Diversity of arbuscular mycorrhizal fungi and its response to seasonal variation in alpine grassland of the eastern Tibetan Plateau - Dong, Wanqing; Ding, Tingting; Duan, Tingyu (Frontiers in Microbiology, 2025)
IntroductionArbuscular mycorrhizal (AM) fungi play a crucial role in maintaining diversity and ensuring the proper functioning of grassland ecosystems. A comprehensive understanding of the diversity, distribution patterns, and drivers of AM fungi in different habitats is essential for exploring the ecological roles in grassland ecosystems.MethodsIn this study, we utilized high-throughput sequencing technology to explore the diversity of AM fungi and their distribution at an altitude of approximately 3,500 m in the alpine grassland of the eastern Tibetan Plateau. Additionally, we investigated the impacts of seasonal variation on AM fungal communities.ResultsA total of 97 species of AM fungi, comprising 937 operational taxonomic units (OTUs) belong to 9 families and 10 genera, were identified from the soil samples. Notably, the genera Glomus and Paraglomus were the most abundant and dominant within the identified communities. The composition, distribution, and diversity of the AM fungal communities in the alpine grassland of the eastern Tibetan Plateau were significantly affected by seasonal variation (p < 0.05), with geographic distance being a determining factor. Total nitrogen (TN), soil organic matter (SOM), and pH were identified as the key soil factors driving changes in AM fungal communities.DiscussionThe results demonstrated that the characteristics of AM fungal communities in the alpine grasslands of the eastern Tibetan Plateau were affected by seasonal variations and geographic location, and these findings are significant for the application of AM fungi in the restoration of grassland in similar ecosystems.